Complete genome sequence of the carotenoid-producing Deinococcus sp. Strain AJ005 - Choi, Jun Young; Lee, Kunjoong; Lee, Pyung Cheon (Microbiology Resource Announcements, 2019)
The novel species Deinococcus sp. strain AJ005, isolated from King George Island, synthesizes a red carotenoid. Its complete genome is made up of a single circular chromosome (3,380,712 bp, 64.2% G+C content) and four circular plasmids.